Pharmaceutical pollution in a changing climate: the influence of temperature and salinity on the toxicity of carbamazepine in Mytilus Galloprovincialis - Bajwa, Farhat-Un-Nisá Nascimento (2024)
The relentless presence of contaminants of emerging concern, such as human pharmaceuticals, in marine and coastal ecosystems has made ocean pollution one of the most pressing challenges of the Anthropocene. The continuous and exacerbated use of pharmaceuticals worldwide has been linked to the ubiquitous presence of different therapeutic classes in marine matrices (e.g., water, sediment and biota), with direct and indirect implications for ocean and human health. Alongside this, the era of climate change exacerbates the interplay of multiple stressors in marine systems through increased seawater temperature and salinity fluctuations, leading to unknown impacts on the marine biota. However, limited information is available on the combined effects of pharmaceuticals in a multiple-stressor marine environment. Psychotropic drugs, such as carbamazepine (CBZ), are consumed for the treatment of epilepsy and some psychiatric disorders. CBZ causes negative effects on marine biota, and its persistence in aquatic ecosystems has been widely studied. A multiple-biomarker approach was employed to assess alterations in energy balance, antioxidant and biotransformation systems, membrane damage, neurotoxicity, and genotoxicity in gills and digestive glands of marine mussels. Therefore, to better understand the combined impacts of CBZ and climate change-driven stressors (increased seawater temperature and salinity), the present study aims to assess the biochemical and genotoxic alterations through an in vivo experiment. For this purpose, marine mussels M. galloprovincialis were exposed to a combination of CBZ (nominal concentration of 5 µg/L) with different temperatures (17° and 23° C) and salinities (35 and 40) for 28 days. The outcomes provide a first insight on the mussel’s responses to CBZ under a changing climate. To best our knowledge, this is the first study to explore the effects of CBZ combined with the rise of seawater temperature and salinity on marine mussels.